2016
DOI: 10.1007/s00705-016-2923-7
|View full text |Cite
|
Sign up to set email alerts
|

HN protein of Newcastle disease virus sensitizes HeLa cells to TNF-α-induced apoptosis by downregulating NF-κB expression

Abstract: Newcastle disease virus (NDV) is an oncolytic virus which selectively replicates in tumor cells and exerts anti-tumor cytotoxic activity by promoting cell death. In this study, we focus on characterization of the underlying mechanisms of NDV-induced cell death in HeLa cells. We find that NDV Herts/33 strain triggers both extrinsic and intrinsic apoptosis at late infection times. The activation of NF-кB pathway and subsequent up-regulation of TNF-α/TRAIL initiates extrinsic apoptosis, leading to activation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Animal experiments implied that TNF‐α suppressed progression to T1DM. Abundant studies demonstrated that TNF‐α could induce apoptosis in various cells, such as HELA cells (Rajmani et al, ), H9c2 cells (Zhao et al, ), and MIN6 cells (Z. H. Cao et al, ). Moreover, TNF‐α is investigated to involve in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments implied that TNF‐α suppressed progression to T1DM. Abundant studies demonstrated that TNF‐α could induce apoptosis in various cells, such as HELA cells (Rajmani et al, ), H9c2 cells (Zhao et al, ), and MIN6 cells (Z. H. Cao et al, ). Moreover, TNF‐α is investigated to involve in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping this in mind, our next aim characterizing rNDV-P05 was to explore whether the virus had the capability or not to induce apoptosis over a panel of tumor cell lines from a variety of tissues. In this study, we have demonstrated that rNDV-P05 was able to induce apoptosis over four from five tested cell lines, which had previously shown susceptibility to NDV (29)(30)(31)(32). In solid tumors, this is important for virotherapy, given that the cell death induced by the virus in the tumor microenvironment can evoke not only local, but also a systemic tumor-specific immune surveillance against primary and metastatic malignant cells.…”
Section: Discussionmentioning
confidence: 78%
“…The relation ‘is disease model for’ indicates that the cell line can be used to study a specific disease, and the disease can but does not have to, be the same as the disease of the patient from whom the cell line cell was derived. For example, HeLa cell can be used as a cell line model to study cervical adenocarcinoma, but it can also be used to study many other diseases such as polio and NewCastle Disease [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%